Meta Analysis: The Effectiveness Of Using Project Based Learning Methods In Vocational Education - Fadillah, Rahmat; Ambiyar, Ambiyar; Giatman, Muhammad; Fadhilah, Fadhilah; Muskhir, Mukhlidi; Effendi, Hansi (Jurnal Pedagogi dan Pembelajaran, 2021)
There are many types of learning models, but not all learning models can accommodate the needs of vocational education and the challenges of the 4.0 industrial revolution, namely encouraging critical thinking and developing practical skills. The purpose of this study was to measure the effectiveness of using project based learning methods in vocational education. The research method used is a meta-analysis method with secondary data types. The research data was obtained based on the results of the post-test control class and the experimental class from several research articles that used the project based learning method in vocational education. A total of 23 articles were reviewed so that the calculation result data was 1.09 using the effect size (ES) formula. The results obtained indicate that the use of project based learning methods in vocational education has a high effect to be applied in learning. Thus, the project based learning method in technology and vocational education is very effective and appropriate to use in learning to produce students who are ready to compete in the world of work and can open business opportunities.